2020
DOI: 10.1016/j.mayocp.2020.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Management of Acute Ischemic Stroke Across the Continuum

Abstract: In this comprehensive contemporary review of acute ischemic stroke management, what is new and different will be highlighted beginning with prehospital stroke systems of care, emergency medical systems, and mobile stroke units, followed by hospital stroke teams, emergency evaluation, telemedicine, and brain and vascular imaging, and finishing with emergency treatments including thrombolysis and mechanical thrombectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 123 publications
0
7
0
Order By: Relevance
“…Given that clinical outcomes are strictly time-sensitive, 5 , 6 , 7 the current early management of patients with AIS is aimed at reducing the time interval between presentation and treatment (with intravenous thrombolysis, MT, or both). 8 , 9 The American Heart Association or American Stroke Association updated their “Target: Stroke Phase III” guidelines for reducing door-to-device times (time interval from arrival at the hospital to first pass with a thrombectomy device), with a goal time of less than 90 minutes for patients arriving directly at the hospital and less than 60 minutes for transfer patients. 10…”
mentioning
confidence: 99%
“…Given that clinical outcomes are strictly time-sensitive, 5 , 6 , 7 the current early management of patients with AIS is aimed at reducing the time interval between presentation and treatment (with intravenous thrombolysis, MT, or both). 8 , 9 The American Heart Association or American Stroke Association updated their “Target: Stroke Phase III” guidelines for reducing door-to-device times (time interval from arrival at the hospital to first pass with a thrombectomy device), with a goal time of less than 90 minutes for patients arriving directly at the hospital and less than 60 minutes for transfer patients. 10…”
mentioning
confidence: 99%
“…Although the "OWH effect" is an accepted phenomenon, the latter does not exclude the pertinence of telestroke management in AIS. As explored by Demaerschalk et al in a recent publication, telestroke, defined in the cited study as a consultation involving audio and video modalities (20), remains one of the best-studied and validated models for telemedicine (21)(22)(23)(24)(25)(26). An approach by telephone consultation and teleradiology by neurovascular experts has also been shown to be safe, similar to the approach adopted in HFR (27).…”
Section: Discussionmentioning
confidence: 93%
“…Studies in the United States found that women experience approximately 55,000 more strokes each year [91], [92], which has been linked to higher life expectancy, hormonal changes, use of contraceptives, and variable risk factors in women [93]- [96]. On the premise of non-modifiable risk factors; age and sex associated with stroke [21], [30], [99], [100], [35], [53], [54], [57], [63], [76], [97], [98], this study found that age group but not sex had direct effect on the stroke type. While the initial analysis found some association between sex and stroke type, the SEM after controlling for several factors, found no significant direct effect.…”
Section: Discussionmentioning
confidence: 99%